Impact of lifestyle and psychological resilience on survival among the oldest-old in China: a cohort study - Jianping Cai; Yumeng Gao; Tingfa Hu; Lv Zhou; Hongye Jiang (Frontiers Media S.A., 2023)
IntroductionHealthy lifestyles and psychological resilience are important factors influencing the life expectancy of the oldest-old (≥80 years). Stratified by urban and rural groups, this study used a 10-year cohort to examine the mechanism of lifestyle and psychological resilience on the survival of the oldest-old in China.MethodsThis study used the China Longitudinal Healthy Longevity Survey datasets spanning from 2008 to 2018, and 9,250 eligible participants were included. The primary outcome variable was all-cause mortality, and independent variables included healthy lifestyle index and psychological resilience. Six covariates were included in the survival analysis and moderation-mediation model, such as gender and annual household income.ResultsThis study found that the oldest-old with five healthy lifestyles had the longest survival time, averaging 59.40 months for urban individuals and 50.08 months for rural individuals. As the lifestyle index increased, the survival rate significantly increased. The Cox regression showed that for the urban oldest-old, the lifestyle index served as a protective factor for survival outcomes. However, this effect lost statistical significance among rural oldest-old individuals. For urban oldest-old individuals, psychological resilience significantly mediated and moderated the effect of the lifestyle index on survival status, but the moderating effect was not statistically significant for the rural ones.DiscussionOverall, healthy lifestyles and psychological resilience can be effective in enhancing the survival of the oldest-old, and there are differences between urban and rural population, so different interventions should be adopted for urban and rural areas to achieve longer life in China.